The Effect of Work Pressure and Affective Commitment on Turnover Intention at PT. Artaboga Cemerlang Manado - Debora F. Lontoh; Frederik G. Worang; Ferdinand J. Tumewu (Universitas Sam Ratulangi, 2022)
Abstract: This study aims to understand and find out if work pressure and affective commitment have an effect on turnover intention at PT. Artaboga Cemerlang Manado employee. This research is using quantitative method. It will explain the relationship of variables through causal analysis in the scale method between two continuous independent variables and one dependent variable. Researcher distributed questionnaires and the sample used was 30 respondents. The result showed both work pressure and affective commitment simultaneously have a significant effect of turnover intention at PT. Artaboga Cemerlang Manado. It can be concluded that the work pressure variable partially has a significant effect on turnover intention and affective commitment partially has a significant effect on the turnover intention at PT. Artaboga Cemerlang Manado. Based on the results it can be said that working pressure and affective commitment have an important role in affecting turnover intention. PT. Artaboga Cemerlang Manado needs to manage well amount of job that they give to their workers and developing human resource strategies to strengthen the level of affective commitment. Keywords: work pressure, affective commitment, turnover intention